Developmental studies of certain South African Ascostromatic ascomycetes - Tim, Stephen K-M (Rhodes University, Faculty of Science, Botany Department, 1971)
From General Introduction: Toward the last half of the nineteenth century, the structure and mode of development of the ascocarp has aroused much interest. De Bary (1887) recognised the fruiting bodies of the Ascomycetes as 'compound sporophores' made up of interwoven hyphae or of pseudoparenchyma consisting of a peripheral layer separate from an inner tissue. These fruiting bodies included the discocarp or apothecium, the pyrenocarp or perithecium and the cleistocarp or cleistothecium. The name, Pyrenomycetes, has been variously applied to a group of Ascomycetes but mainly to the perithecial types, inclusive of the true perithecia and the loculate forms. The perithecium itself was described as a 'cup-shaped discomycetous' sporocarp with margins incurved to form a pyriform structure (de Bary, 1887). The presence or absence of a stroma had been long considered as a basis for the separation of the major groups of the Ascomycetes. Separation on these grounds was found unacceptable as it grouped together clearly unrelated species or separated related ones. As the subdivisions of the pyrenomycetous Ascomycetes are dependent upon the morphological features of the ascocarp, it would be pertinent to discuss the following: a) The Stroma. b) The various forms of ascocarp which mayor may not be associated with such a stroma. i) Perithecia: free or immersed in a stroma. ii) Uni- or multiloculate stromata. c) The centrum, the details associated with the centrum and the use of these details in the taxonomy of the pyrenomycetes.
Keywords: Fungi -- Parasites; Ascomycetes; Pyrenomycetes -- South Africa